Radiotherapy and immune response: the systemic effects of a local treatment - Carvalho, Heloisa de Andrade; Villar, Rosangela Correa (Clinics, 2019)
Technological developments have allowed improvements in radiotherapy delivery, with higher precision and better sparing of normal tissue. For many years, it has been well known that ionizing radiation has not only local action but also systemic effects by triggering many molecular signaling pathways. There is still a lack of knowledge of this issue. This review focuses on the current literature about the effects of ionizing radiation on the immune system, either suppressing or stimulating the host reactions against the tumor, and the factors that interact with these responses, such as the radiation dose and dose / fraction effects in the tumor microenvironment and vasculature. In addition, some implications of these effects in cancer treatment, mainly in combined strategies, are addressed from the perspective of their interactions with the more advanced technology currently available, such as heavy ion therapy and nanotechnology